1975
DOI: 10.1104/pp.55.5.932
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Comparisons of Stomatal Behavior, Water Status, and Evaporation of Maize in Soil at High or Low Water Potential

Abstract: Concurrent measurements of evaporation, leaf conductance, irradiance, leaf water potential, and osmotic potential of maize (Zea mays L. cv. Pa6O2A) in soil at either high or low soil water potential were compared at several hours on two consecutive days in July. Hourly evaporation, measured on two weighing lysimeters, was similar until 1000 hours Eastern Standard Time, but thereafter evaporation from the maize in the dry soil was always less than that in the wet soil; before noon it was 62 % and by midafternoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
1

Year Published

1976
1976
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 15 publications
2
13
1
Order By: Relevance
“…3e;4e). In a study carried out on field grown maize, Turner (1975) observed a stomatal closure when leaf water potential dropped to values lower than -1.50 MPa. In our case, midday w l measured on 54 DAS, dropped to -1.88 MPa, thus indicating that a stomatal closure was occurred limiting ecosystem gas exchange.…”
Section: Discussionmentioning
confidence: 96%
“…3e;4e). In a study carried out on field grown maize, Turner (1975) observed a stomatal closure when leaf water potential dropped to values lower than -1.50 MPa. In our case, midday w l measured on 54 DAS, dropped to -1.88 MPa, thus indicating that a stomatal closure was occurred limiting ecosystem gas exchange.…”
Section: Discussionmentioning
confidence: 96%
“…Prior to each harvest, the area of each leaf blade on every plant was estimated in situ from the measured length and width, multiplied by a scaling factor of 0.69 for sorghum (Lafarge and Hammer 2002) and 0.75 for maize (Turner 1975). At harvest, the shoot of each plant was cut at the base of the stem, and separated into stem (including leaf sheath) and leaf blade fractions.…”
Section: Experiments 1: Initiation Of Roots At Germinationmentioning
confidence: 99%
“…Diurnal osmotic adjustment has been reported in some higher plants (Turner, 1975;Cutler & Raines, 1978;Wenkert, Lemon & Sinclair, 1978;Cutler, Shahan & Steponkus, 1980) but it has been found to be insignificant in others (Hinckley et al, 1980). Rapid changes in plant water potential due to a drop in turgor pressure in response to a small water loss are known to occur in leaves with relatively inelastic cell walls (Tyree, 1976;Tyree & Karamanos, 1980;Salleo & Lo Gullo, 1985;Lo Gullo et al, 1986) and are likely to be useful in plants subjected to shortterm water stress (changing in intensity, for instanee, with a nictemeral rhythm).…”
Section: Introductionmentioning
confidence: 99%